Speed Control of Single Phase Induction Motor Using TRIAC and RPM Measurement by Contactless Tachometer - Bhardwaj, Shubham; Varshney, Yuvraj; Sharma, Kasa v; Bhardwaj, Utkarsh (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
The main aim of this project is to control the speed of an induction motor by applying varying voltages to the motor by using TRIAC. The project uses zero crossing point of the waveform which is detected by a comparator whose output is then fed to the microcontroller. The microcontroller provides required delayed triggering control to TRIAC through opto isolator interface. Finally the power is applied to the load through a TRIAC. This project uses a microcontroller from 2051 family which is interfaced through two push-button switches for increasing or decreasing the AC power to the load. The varying power shall result in variation in the speed of the motor while the lamp is replaced by the single phase induction motor.IR sensor used for transmitting the signal to white portion on the rotor and photo diode receive the signal then it send to the 8051 microcontroller then LCD display used to display the speed level of Ac load.